Validation of dermal patches as a non-invasive tool for monitoring amphibian steroid hormones - Dimovski, Alicia M.; Silla, Aimee J.; Nimmo, Emily; Fanson, Kerry V. (Frontiers in Conservation Science, 2025)
Global amphibian populations are declining, driven by a complex interplay of stressors including habitat destruction, climate change, pollutants, invasive species, and emergent diseases. Understanding the physiological response of amphibians to these stressors is critical, and hormones offer a powerful lens into their reproductive health and stress resilience. However, our knowledge of amphibian physiology and endocrinology remains limited, largely due to the lack of suitable non-invasive monitoring tools. Here, we present an innovative, non-invasive hormone monitoring method using small, temporary dermal patches. First, we evaluated six patch materials and two extraction techniques for their effectiveness in measuring corticosterone and testosterone. Our results indicate that patch performance varied depending on both the hormone type and extraction method. Second, to biologically validate this approach for monitoring dermal androgens, we monitored changes in testosterone levels in the Blue Mountains tree frog (Dryopsophus citropa) following the administration of human chorionic gonadotropin (hCG). Dermal patches successfully detected biologically relevant increases in testosterone post-stimulation, confirming their utility for monitoring reproductive hormones. This novel technique provides a viable, non-invasive approach for assessing amphibian steroid hormones, creating new opportunities to advance amphibian physiological research, ecological monitoring, and conservation management.